Mass concrete with low hydration peak temperature and preparation method thereof
By using boron nitride ceramic aggregate in large volumes of concrete, the sharp temperature rise and resource shortage caused by hydration reaction are solved, the crack resistance and durability of concrete are improved, and the engineering cost and environmental impact are reduced.
Patent Information
- Application Number
- CN202411324776.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the solidification and molding process, the hydration reaction of large-volume concrete exothermic heat causes a sharp rise in temperature, resulting in temperature cracks and shortage of resources.
Ceramics are coated with boron nitride phase change heat storage materials to prepare boron nitride ceramic aggregates, replacing some natural coarse aggregates, reducing the peak hydration temperature and delaying the hydration and exothermic behavior.
Effectively reduce the formation rate of temperature cracks inside large-volume concrete, improve crack resistance and durability, and at the same time reduce the demand for natural resources and reduce engineering costs and environmental impact.
Smart Images

Figure CN119241162A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a mass concrete with a low hydration peak temperature and a preparation method thereof. Background Art
[0002] With the rapid development of my country's economy, the investment in infrastructure and construction projects has gradually increased, and more and more large-scale and super-large construction projects and large-area and large-volume concrete foundation projects have emerged. As an important structural form in modern engineering construction, mass concrete has been widely used in construction projects such as high-rise buildings, water conservancy and hydropower projects, bridges and port buildings. However, after the mass concrete is poured, the hydration reaction of the cement inside it will release a large amount of hydration heat, causing the temperature inside the structure to rise sharply. At the same time, due to the poor thermal conductivity of mass concrete, a large amount of heat energy is difficult to dissipate in time, resulting in an imbalance in the temperature distribution inside and outside the concrete, forming temperature stress, and then inducing temperature cracks inside the concrete, seriously affecting the service performance and durability of the concrete structure.
[0003] In view of the technical difficulties of large-volume concrete, such as large heat release and high internal peak temperature in the hydration reaction, the commonly used cooling methods for large-volume concrete in engineering construction are: (1) pre-cooling the raw materials of concrete; (2) mixing concrete with cold water; (3) curing by heat preservation and moisture retention; (4) pre-burying cooling water pipes inside large-volume concrete. However, these cooling methods also have some disadvantages, such as complicated processes, affecting the service performance of large-volume concrete, and causing an increase in engineering construction costs. In addition, as one of the most widely used building materials in the world today, concrete has a large demand for natural raw materials such as gravel and river sand. The large-scale mining of natural river sand will aggravate the increasing shortage of natural resources and seriously affect the structural safety and ecological balance of my country's rivers.
[0004] Therefore, the present invention proposes a new type of mass concrete with low hydration peak temperature and a preparation method thereof, adopts ceramsite-coated boron nitride phase change heat storage material to prepare boron nitride ceramsite aggregate with high heat storage performance, and partially replaces the natural coarse aggregate component in the mass concrete, which can effectively reduce the hydration peak temperature of the mass concrete, delay the hydration exothermic behavior of the mass concrete, reduce the formation rate of temperature cracks inside the mass concrete, solve the problem of rapid hydration temperature rise of the mass concrete during the solidification and molding process and the problem of increasing shortage of natural aggregate resources, and has significant social, economic and environmental benefits. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a mass concrete with a low hydration peak temperature and a preparation method thereof, which can effectively reduce the hydration peak temperature of the mass concrete, delay the hydration exothermic behavior of the mass concrete, reduce the formation rate of temperature cracks inside the mass concrete, and solve the problem of rapid hydration temperature rise of the mass concrete during the solidification and molding process and the problem of the increasing shortage of natural aggregate resources.
[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:
[0007] A mass concrete with a low hydration peak temperature, comprising raw materials by weight: 150-200 parts of cement, 80-130 parts of fly ash, 30-70 parts of slag powder, 500-700 parts of crushed stone, 200-350 parts of boron nitride ceramsite aggregate, 800-1000 parts of sand, 150-200 parts of water, and 5-10 parts of admixture; wherein the preparation method of the boron nitride ceramsite aggregate is as follows:
[0008] (1) Fly ash, municipal sludge and silt are crushed and dried; boron nitride is screened so that the mass ratio of particles with a size of 5-20 μm and 20-50 μm is (6-7): (3-4);
[0009] (2) The treated fly ash, urban sewage sludge and silt are mixed uniformly in a mass ratio of (3-5): (3-5): (1-3), and boron nitride is added and mixed uniformly to obtain ceramsite raw material; the amount of boron nitride used is 3%-20% of the total mass of fly ash, urban sewage sludge and silt;
[0010] (3) Place the ceramsite raw material in a container, add an inorganic pore-forming agent and an appropriate amount of water, mix well, and age for 30 to 60 minutes;
[0011] (4) The aged ceramsite raw material is granulated and sintered to obtain type A boron nitride ceramsite with a particle size range of 5-20 mm and type B boron nitride ceramsite with a particle size range of 20-31.5 mm. The type A and type B boron nitride ceramsite are mixed in a mass ratio of (6-7):(3-4) to obtain boron nitride ceramsite aggregate.
[0012] Preferably, the technical index of the boron nitride ceramsite aggregate is: apparent density ≤ 1900 kg / m 3 ; Bulk density ≤700 kg / m 3 ; Cylinder pressure strength ≥5 MPa; Strength ≥40 MPa; Water absorption rate in 1h ≤15%.
[0013] Preferably, the specific operation of the sintering is: placing the ceramsite raw material particles in an oven, controlling the temperature to 105±5°C, and drying for 30-40 min; then placing the ceramsite raw material particles in a high-temperature furnace, adjusting the temperature to 500-600°C, and preheating for 30-40 min; after the preheating, adjusting the temperature to 1150-1250°C for sintering for 30-40 min, and reducing the temperature to room temperature at a rate of ≤3°C / min to obtain type A and type B boron nitride ceramsite.
[0014] Preferably, the fly ash is Class F, Grade II fly ash recovered from a coal-fired power plant, and the fly ash particle size is ≤0.9 mm.
[0015] Preferably, the municipal sludge or silt is municipal sludge or silt that has been filtered, adsorbed, precipitated and separated.
[0016] Preferably, the water content of the crushed and dried municipal sludge or mud is ≤1%, and the particle size is ≤0.8 mm.
[0017] Preferably, the boron nitride is one or more of hexagonal boron nitride, cubic boron nitride or wurtzite boron nitride, the boron nitride particle size is 5-50 μm, the purity is ≥99%, and the apparent density is 2300-3450 kg / m 3 .
[0018] Further preferably, the hexagonal boron nitride is prepared by one of the following three methods: reaction of borax with ammonium chloride, reaction of boric anhydride-tricalcium phosphate pellets with ammonia, reaction of borax with urea, and purification treatment is required after the reaction; the cubic boron nitride or wurtzite boron nitride is prepared by hexagonal boron nitride under high temperature and high pressure.
[0019] Preferably, the air flow rate generated by the airflow sieving device used for the sieving is 30-120 m 3 / h, the speed is 5~30rpm, and the screen can be cleaned automatically.
[0020] Preferably, the water is tap water for urban life.
[0021] Preferably, the inorganic pore-forming agent is one or a mixture of carbon powder, calcium carbonate and magnesium carbonate.
[0022] Preferably, the amount of the inorganic pore-forming agent is 6% to 8% of the mass of the ceramsite raw material.
[0023] Preferably, the container is an iron cylindrical container with a wall thickness of 10 to 20 mm.
[0024] Preferably, the moisture content of the aged ceramsite raw material is 10% to 15%.
[0025] Preferably, the granulator used for the granulation is one of a double-die extrusion granulator, a pot granulator, and a rotary granulator.
[0026] The method for preparing the mass concrete with low hydration peak temperature comprises the following steps:
[0027] S1. Pre-wet the boron nitride ceramsite aggregate for 1-2 h;
[0028] S2, adding cement, sand, fly ash and slag powder into a concrete mixer in sequence and mixing them evenly;
[0029] S3, adding crushed stone and boron nitride ceramsite aggregate into a concrete mixer and mixing them evenly;
[0030] S4. Add the admixture into water, mix well, then pour into a concrete mixer and mix well to obtain a large volume concrete with a low hydration peak temperature.
[0031] Preferably, the cement is one of P·O 42.5 grade silicate cement, P·LH 42.5 grade low heat silicate cement, and P·MH 42.5 grade medium heat silicate cement.
[0032] Preferably, the fly ash is Class F, Grade II fly ash recovered from a coal-fired power plant, and the particle size of the fly ash is ≤0.9 mm.
[0033] Preferably, the slag powder is S95 grade granulated blast furnace slag powder.
[0034] Preferably, the crushed stone has a particle size of 5 to 31.5 mm and a continuously graded crushed stone with an apparent density of 2700 to 2800 kg / m 3 , bulk density is 1500~1600 kg / m 3 .
[0035] Preferably, the sand is medium sand, with a fineness modulus of 2.3-2.5, a mud content of ≤3%, and an apparent density of about 2600-2700 kg / m 3 .
[0036] Preferably, the admixture is a slow-setting polycarboxylate water-reducing agent.
[0037] Compared with the prior art, the present invention is beneficial in that:
[0038] (1) The present invention uses ceramsite as a carrier to prepare boron nitride ceramsite aggregate, which is then uniformly mixed into large-volume concrete. The boron nitride ceramsite aggregate with a smaller particle size can quickly absorb a large amount of hydration heat energy generated during the cement hydration reaction, thereby reducing the concrete hydration temperature rise rate and peak temperature. The boron nitride ceramsite aggregate with a larger particle size can absorb more hydration heat energy, and the heat storage effect is more obvious, which delays the post-peak temperature rise behavior, and can significantly alleviate the problem of heat dissipation difficulty in large-volume concrete, reduce the heat accumulation inside it, weaken the interaction between the raw material components, improve the crack resistance of large-volume concrete, and significantly improve the mechanical properties and durability of large-volume concrete.
[0039] (2) The method for preparing a large-volume concrete with a low hydration peak temperature provided by the present invention is relatively simple in casting method in actual engineering compared with the method for preparing ordinary large-volume concrete. There is no need to pre-cool the raw materials, use cold water for stirring, or arrange cooling water pipes, which can effectively reduce the construction cost of the actual engineering.
[0040] (3) The present invention prepares boron nitride ceramsite aggregate to partially replace natural coarse aggregate in large-volume concrete, thereby significantly reducing the demand for natural resources for concrete materials; the present invention uses urban sludge and silt to prepare boron nitride ceramsite aggregate, which can effectively reduce the stock of urban sludge and silt, reduce the storage cost and treatment cost of urban sludge and silt, and has significant environmental significance and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The temperature changes of each measuring point in Example 1, Comparative Example 1, Comparative Example 3 and Comparative Example 4 are shown. DETAILED DESCRIPTION
[0042] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The invention provides a mass concrete with a low hydration peak temperature. The raw materials include, by weight, 150-200 parts of cement, 80-130 parts of fly ash, 30-70 parts of slag powder, 500-700 parts of crushed stone, 200-350 parts of boron nitride ceramsite aggregate, 800-1000 parts of sand, 150-200 parts of water, and 5-10 parts of admixture; wherein the preparation method of the boron nitride ceramsite aggregate is as follows:
[0044] (1) Fly ash, municipal sludge and silt are crushed and dried; boron nitride is screened so that the mass ratio of particles with a size of 5-20 μm and 20-50 μm is (6-7): (3-4);
[0045] (2) The treated fly ash, urban sewage sludge and silt are mixed uniformly in a mass ratio of (3-5): (3-5): (1-3), and boron nitride is added and mixed uniformly to obtain ceramsite raw material; the amount of boron nitride used is 3%-20% of the total mass of fly ash, urban sewage sludge and silt;
[0046] (3) Place the ceramsite raw material in a container, add an inorganic pore-forming agent and an appropriate amount of water, mix well, and age for 30 to 60 minutes;
[0047] (4) The aged ceramsite raw material is granulated and sintered to obtain type A boron nitride ceramsite with a particle size range of 5-20 mm and type B boron nitride ceramsite with a particle size range of 20-31.5 mm. The type A and type B boron nitride ceramsite are mixed in a mass ratio of (6-7):(3-4) to obtain boron nitride ceramsite aggregate.
[0048] In some examples, the technical indicators of the boron nitride ceramsite aggregate are: apparent density ≤ 1900 kg / m 3 ; Bulk density ≤700 kg / m 3 ; Cylinder pressure strength ≥5 MPa; Strength ≥40 MPa; Water absorption rate in 1h ≤15%.
[0049] In some examples, the boron nitride is one or more of hexagonal boron nitride, cubic boron nitride or wurtzite boron nitride, the boron nitride has a particle size of 5-50 μm, a purity of ≥99%, and an apparent density of 2300-3450 kg / m 3 .
[0050] In some examples, the inorganic pore former is one or a mixture of carbon powder, calcium carbonate, and magnesium carbonate.
[0051] In some examples, the amount of the inorganic pore former is 6% to 8% of the mass of the ceramsite raw material.
[0052] In some examples, the moisture content of the aged ceramsite raw material is 10% to 15%.
[0053] In some examples, the granulator used for the granulation is one of a double-die extrusion granulator, a pan granulator, and a rotary granulator.
[0054] In a specific embodiment, unless otherwise specified, the fly ash is Class F II fly ash recovered from a coal-fired power plant, and its particle size is ≤0.9 mm; the urban sludge and sludge are urban sludge and sludge after filtration, adsorption, precipitation and separation; the moisture content of the urban sludge or sludge after crushing and drying is ≤1%, and the particle size is ≤0.8 mm; the chemical composition of the sludge after crushing and drying is SiO2 56.84%, Al2O3 22.98%, MgO 2.63%, CaO4.16%, Fe2O3 10.84%, ZnO 0.04%, K2O 1.03%, and TiO2 1.02%; the chemical composition of the sludge after crushing and drying is SiO2 71.61%, Al2O3 14.96%, Fe2O3 5.16%, K2O 2.25%, CaO 1.55%, Na2O1.54%, MgO 1.23%, TiO2 0.952%, P2O5 0.327%, MnO 0.173%; the boron nitride is hexagonal boron nitride, with a particle size of 5-50 μm, a purity of 99.5%, and an apparent density of 2300 kg / m 3 The air flow rate generated by the airflow sieving instrument used for the screening is 30~120 m 3 / h, the rotation speed is 5-30 rpm, and the screen can be automatically cleaned; the water used for aging is tap water for urban life; the inorganic pore-forming agent is calcium carbonate, and the dosage is 7% of the mass of the ceramsite raw material; the moisture content of the aged ceramsite raw material is 13%; the container is an iron cylindrical container with a wall thickness of 10-20 mm; the granulator used for granulation is a double-die extrusion granulator.
[0055] The method for preparing the mass concrete with low hydration peak temperature comprises the following steps:
[0056] S1. Pre-wet the boron nitride ceramsite aggregate for 1-2 h;
[0057] S2, adding cement, sand, fly ash and slag powder into a concrete mixer in sequence and mixing them evenly;
[0058] S3, adding crushed stone and boron nitride ceramsite aggregate into a concrete mixer and mixing them evenly;
[0059] S4. Add the admixture into water, mix well, then pour into a concrete mixer and mix well to obtain a large volume concrete with a low hydration peak temperature.
[0060] In some examples, the cement is one of P·O 42.5 grade silicate cement, P·LH 42.5 grade low heat silicate cement, and P·MH 42.5 grade medium heat silicate cement.
[0061] In a specific embodiment, unless otherwise specified, the cement is P·O 42.5 grade silicate cement; the fly ash is Class F Class II fly ash recovered from a coal-fired power plant, and its particle size is ≤0.9 mm; the slag powder is S95 grade granulated blast furnace slag powder; the crushed stone is a continuously graded crushed stone with a particle size of 5 to 31.5 mm and an apparent density of 2750 kg / m 3 , bulk density is 1600 kg / m 3 The sand is medium sand, with a fineness modulus of 24, a mud content of 1%, and an apparent density of about 2650 kg / m 3 ; The admixture is a slow-setting polycarboxylic acid water-reducing agent.
[0062] Example 1
[0063] A mass concrete with low hydration peak temperature includes the following weight components: 170 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 600 parts of crushed stone, 350 parts of boron nitride ceramsite aggregate, 900 parts of sand, 170 parts of water, and 7 parts of admixture. The preparation steps are as follows:
[0064] (1) Fly ash, municipal sludge and silt were crushed and dehydrated; boron nitride was sieved for 2 min using an airflow sieving instrument to make the mass ratio of particles in the range of 5-20 μm and 20-50 μm to be 7:3;
[0065] (2) The fly ash, municipal sludge and silt after crushing and drying are mixed in a mass ratio of 5:3:2, and 10% of boron nitride is added to obtain ceramsite raw material;
[0066] (3) Pour the ceramsite raw material into a container, add an inorganic pore-forming agent and an appropriate amount of water, stir evenly, and age for 60 min;
[0067] (4) Granulate the aged ceramsite raw material, place the ceramsite raw material particles in an oven, control the oven temperature to 105±5℃, and dry them for 30 min; then place the ceramsite raw material particles in a high-temperature furnace, adjust the temperature to 600℃, and preheat for 30 min; after the preheating, adjust the temperature to 1200℃ and sinter for 40 min, cool the temperature to room temperature at a rate of 3℃ / min, and obtain type A boron nitride ceramsite with a particle size range of 5-20 mm and type B boron nitride ceramsite with a particle size range of 20-31.5 mm. The type A and type B boron nitride ceramsite are mixed in a mass ratio of 7:3 to obtain boron nitride ceramsite aggregate. The technical indicators of the boron nitride ceramsite aggregate are shown in Table 1;
[0068] (5) Pre-wetting the boron nitride ceramsite aggregate for 1 h;
[0069] (6) Add cement, sand, fly ash and slag powder into the concrete mixer in sequence and stir for 2 minutes to mix evenly;
[0070] (7) Add crushed stone and boron nitride ceramsite aggregate into the concrete mixer and stir for 2 minutes to mix evenly;
[0071] (8) Add the admixture to water, stir evenly, then pour into a concrete mixer and continue stirring for 2 minutes to obtain a large volume concrete with a low hydration peak temperature.
[0072] Table 1: Technical indicators of boron nitride ceramsite aggregate
[0073]
[0074] Comparative Example 1
[0075] A mass concrete with low hydration peak temperature includes the following weight components: 170 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 600 parts of crushed stone, 350 parts of boron nitride ceramsite aggregate, 900 parts of sand, 170 parts of water, and 7 parts of admixture. The preparation steps are as follows:
[0076] (1) Fly ash, municipal sludge and silt were crushed and dehydrated; boron nitride was sieved for 2 min using an airflow sieving instrument to make the mass ratio of particles in the range of 5-20 μm and 20-50 μm to be 7:3;
[0077] (2) The fly ash, municipal sludge and silt after crushing and drying are mixed in a mass ratio of 5:3:2, and 10% of boron nitride is added to obtain ceramsite raw material;
[0078] (3) Pour the ceramsite raw material into a container, add an inorganic pore-forming agent and an appropriate amount of water, stir evenly, and age for 60 min;
[0079] (4) Granulating the aged ceramsite raw material, placing the ceramsite raw material particles in an oven, controlling the oven temperature to 105±5℃, and drying for 30 min; then placing the ceramsite raw material particles in a high-temperature furnace, adjusting the temperature to 600℃, and preheating for 30 min; after the preheating, adjusting the temperature to 1200℃ and sintering for 40 min, cooling the temperature to room temperature at a rate of 3℃ / min, and obtaining boron nitride ceramsite aggregate with a particle size range of 5~20 mm;
[0080] (5) Pre-wetting the boron nitride ceramsite aggregate for 1 h;
[0081] (6) Add cement, sand, fly ash and slag powder into the concrete mixer in sequence and stir for 2 minutes to mix evenly;
[0082] (7) Add crushed stone and boron nitride ceramsite aggregate into the concrete mixer and stir for 2 minutes to mix evenly;
[0083] (8) Add the admixture to water, stir evenly, then pour into a concrete mixer and continue stirring for 2 minutes to obtain large-volume concrete.
[0084] Comparative Example 2
[0085] A mass concrete with low hydration peak temperature includes the following weight components: 170 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 600 parts of crushed stone, 350 parts of ceramsite aggregate, 900 parts of sand, 170 parts of water, and 7 parts of admixture. The preparation steps are as follows:
[0086] (1) Crushing, dehydrating and drying fly ash, urban sludge and silt;
[0087] (2) The fly ash, municipal sludge and silt after crushing and drying are mixed in a mass ratio of 5:3:2 to obtain ceramsite raw material; the ceramsite raw material is poured into a container, an inorganic pore-forming agent and an appropriate amount of water are added, stirred evenly, and aged for 60 minutes;
[0088] (3) Granulate the aged ceramsite raw material, place the ceramsite raw material particles in an oven, control the oven temperature to 105±5℃, and dry them for 30 min; then place the ceramsite raw material particles in a high-temperature furnace, adjust the temperature to 600℃, and preheat them for 30 min; after the preheating, adjust the temperature to 1200℃ and sinter for 40 min, cool the temperature to room temperature at a rate of 3℃ / min, and obtain type A ceramsite with a particle size range of 5-20 mm and type B ceramsite with a particle size range of 20-31.5 mm. Type A and type B ceramsite are mixed in a mass ratio of 7:3 to obtain ceramsite aggregate;
[0089] (5) Pre-wetting the ceramsite aggregate for 1 h;
[0090] (6) Add cement, sand, fly ash and slag powder into the concrete mixer in sequence and stir for 2 minutes to mix evenly;
[0091] (7) Add crushed stone and boron nitride ceramsite aggregate into the concrete mixer and stir for 2 minutes to mix evenly;
[0092] (8) Add the admixture to water, stir evenly, then pour into a concrete mixer and continue stirring for 2 minutes to obtain large-volume concrete.
[0093] Comparative Example 3
[0094] A large volume concrete, with the proportion of boron nitride ceramsite aggregate added adjusted, includes the following weight components: 170 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 800 parts of crushed stone, 150 parts of boron nitride ceramsite aggregate, 900 parts of sand, 170 parts of water, and 7.2 parts of admixture. The preparation steps are as follows:
[0095] (1) Fly ash, municipal sludge and silt were crushed and dehydrated; boron nitride was sieved for 2 min using an airflow sieving instrument to make the mass ratio of particles in the range of 5-20 μm and 20-50 μm to be 7:3;
[0096] (2) The fly ash, municipal sludge and silt after crushing and drying are mixed in a mass ratio of 5:3:2, and 10% of boron nitride is added to obtain ceramsite raw material;
[0097] (3) Pour the ceramsite raw material into a container, add an inorganic pore-forming agent and an appropriate amount of water, stir evenly, and age for 60 min;
[0098] (4) Granulate the aged ceramsite raw material, place the ceramsite raw material particles in an oven, control the oven temperature to 105±5℃, and dry them for 30 min; then place the ceramsite raw material particles in a high-temperature furnace, adjust the temperature to 600℃, and preheat for 30 min; after the preheating, adjust the temperature to 1200℃ and sinter for 40 min, cool the temperature to room temperature at a rate of 3℃ / min, and obtain type A boron nitride ceramsite with a particle size range of 5-20 mm and type B boron nitride ceramsite with a particle size range of 20-31.5 mm. Type A and type B boron nitride ceramsite are mixed in a mass ratio of 7:3 to obtain boron nitride ceramsite aggregate;
[0099] (5) Pre-wetting the boron nitride ceramsite aggregate for 1 h;
[0100] (6) Add cement, sand, fly ash and slag powder into the concrete mixer in sequence and stir for 2 minutes to mix evenly;
[0101] (7) Add crushed stone and boron nitride ceramsite aggregate into the concrete mixer and stir for 2 minutes to mix evenly;
[0102] (8) Add the admixture to water, stir evenly, then pour into a concrete mixer and continue stirring for 2 minutes to obtain a large volume concrete with a low hydration peak temperature.
[0103] Comparative Example 4
[0104] A large volume concrete includes the following weight components: 170 parts of cement, 100 parts of fly ash, 50 parts of slag powder, 950 parts of crushed stone, 900 parts of sand, 170 parts of water, and 7.3 parts of admixture. The preparation steps are as follows:
[0105] (1) Add cement, sand, fly ash and slag powder into the concrete mixer in sequence and stir for 2 minutes to mix them evenly;
[0106] (2) Add the crushed stone into the concrete mixer and mix for 2 minutes until it is evenly mixed;
[0107] (3) Add the admixture to water, stir evenly, then pour into a concrete mixer and continue stirring for 2 minutes to prepare large-volume concrete.
[0108] In order to compare and analyze the technical advantages of the mass concrete with low hydration peak temperature of the present invention, the following test method is used to study its hydration temperature rise during the curing period and determine the temperature-age distribution relationship at each characteristic point inside or on the surface:
[0109] After the concrete mixing is completed, the fresh concrete is poured into a 1 m×1 m×1 m cubic mold and a 150 mm×150 mm×150 mm cubic mold, which are used to monitor its hydration temperature rise and conduct 28-day compressive strength tests, respectively. The measured temperature of the concrete entering the mold is 30.2℃. Plastic film and thermal insulation cotton are covered on the specimen mold to reduce the influence of the external environment temperature change on the internal temperature of the specimen. The specimen is watered and cured 12 hours after the pouring is completed. Three measuring points are arranged on the upper, middle, bottom and side of the 1m×1 m×1 m cubic mold. Each measuring point is represented by F1, F2 and F3, which are located 50 mm below the center of the mold surface, 50 mm above the center of the mold center and the bottom of the mold, respectively. The hydration temperature rise of the concrete is monitored by pre-buried thermocouples. The temperature acquisition frequency is set to 3 h / time within 3 days of curing, and the temperature acquisition frequency is set to 6 h / time after 3 days of curing, and the collection is carried out until 10 days of curing. During the curing period, the temperature changes of each measuring point in each group of specimens are as follows: Figure 1 The 28 d compressive strength of each group of concrete specimens is shown in Table 2.
[0110] Table 2: 28 d compressive strength of concrete specimens in each group
[0111]
[0112] As can be seen from Table 2, the compressive strength of Example 1 and Comparative Example 3 is respectively reduced by about 4.9MPa and 2.9MPa compared with Comparative Example 4; when the amount of boron nitride ceramsite aggregate is less, the decrease in the compressive strength of concrete is smaller. This is because in order to reduce the hydration temperature rise inside the large volume concrete, the patent of the present invention uses boron nitride ceramsite aggregate to replace part of the coarse aggregate in the concrete, resulting in a slight decrease in its compressive strength. Compared with Comparative Example 2, the compressive strength of Example 1 is increased by about 0.4MPa. This is because boron nitride itself has better physical properties. It is added to ceramsite aggregate as a reinforcing phase, which can improve the overall physical properties of boron nitride ceramsite aggregate, thereby improving the compressive strength of concrete.
[0113] from Figure 1 It can be seen that the temperature changes of each group of concrete specimens during the curing period can be divided into a rising period and a falling period. The temperature rise rate at various locations inside Example 1 and Comparative Example 3 is more gentle during the rising period than that of Comparative Example 4, and as the amount of boron nitride ceramsite aggregate increases, the temperature rise rate inside the concrete has an obvious slowing trend. At the same time, during the falling period, the temperature at various locations inside Example 1 and Comparative Example 3 showed an obvious backward shift trend, and the post-peak temperature rise behavior was effectively delayed, indicating that boron nitride ceramsite aggregate, as a phase-change heat storage material, can significantly reduce the degree of hydration temperature rise inside large-volume concrete by evenly distributing inside the concrete to absorb cement hydration heat. In addition, from Figure 1 It can also be found that after the internal temperature of Comparative Example 1 reaches the peak, the temperature reduction rate is slower than that of Example 1. This is because compared with the boron nitride ceramsite aggregate with a particle size of 5-20 mm, the boron nitride ceramsite aggregate with a particle size of 20-31.5 mm has a larger volume and better heat storage performance, while only boron nitride ceramsite aggregate with a particle size of 5-20 mm is added in Comparative Example 1, which makes the post-peak temperature drop process slower.
[0114] By comparing the temperatures of various measuring points in the concrete, it can be found that during the curing period, the temperature at the inner center of each group of concrete is the highest; the inner center peak temperatures of Example 1 and Comparative Example 3 can be reduced by about 3°C and 5°C compared with Comparative Example 4, respectively, indicating that the exothermic behavior of the cement hydration reaction inside the concrete has been significantly delayed, and the formation rate of internal cracks has been effectively controlled, which is beneficial to its durability.
[0115] In summary, the present invention uses fly ash, urban sludge, silt and boron nitride as raw materials to prepare boron nitride ceramsite aggregate, and uses the boron nitride ceramsite aggregate to replace part of the natural aggregate for preparing mass concrete, which can effectively reduce the hydration peak temperature of the mass concrete, delay the hydration exothermic behavior of the mass concrete, reduce the formation rate of temperature cracks inside the mass concrete, and solve the problem of rapid hydration temperature rise of the mass concrete during the solidification and molding process and the problem of increasing shortage of natural aggregate resources.
[0116] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A mass concrete with low hydration peak temperature, characterized in that: The raw materials include, by weight: 150-200 parts of cement, 80-130 parts of fly ash, 30-70 parts of slag powder, 500-700 parts of crushed stone, 200-350 parts of boron nitride ceramsite aggregate, 800-1000 parts of sand, 150-200 parts of water, and 5-10 parts of admixture; wherein the preparation method of the boron nitride ceramsite aggregate is as follows: (1) Fly ash, municipal sludge and silt are crushed and dried; boron nitride is screened so that the mass ratio of particles in the range of 5-20 μm and 20-50 μm is (6-7): (3-4); (2) The treated fly ash, urban sludge and sludge are mixed evenly, and boron nitride is added and mixed evenly to obtain ceramsite raw material; the amount of boron nitride used is 3% to 20% of the total mass of fly ash, urban sludge and sludge; (3) Evenly mix the ceramsite raw material, inorganic pore-forming agent and appropriate amount of water, and age them; (4) The aged ceramsite raw material is granulated and sintered to obtain type A boron nitride ceramsite with a particle size range of 5 to 20 mm and type B boron nitride ceramsite with a particle size range of 20 to 31.5 mm. The type A and type B boron nitride ceramsite are uniformly mixed in a mass ratio of (6 to 7): (3 to 4) to obtain boron nitride ceramsite aggregate.
2. The mass concrete with low hydration peak temperature according to claim 1, characterized in that: The technical index of the boron nitride ceramsite aggregate is: apparent density ≤ 1900 kg / m 3 ; Bulk density ≤700 kg / m 3 ; Cylinder pressure strength ≥5MPa; Strength ≥40 MPa; Water absorption rate in 1h ≤15%.
3. The mass concrete with low hydration peak temperature according to claim 1, characterized in that: In step (2), the mass ratio of fly ash, municipal sludge and silt is (3-5): (3-5): (1-3).
4. The mass concrete with low hydration peak temperature according to claim 1, characterized in that: In step (3), the aging time is 30 to 60 minutes.
5. The mass concrete with low hydration peak temperature according to claim 1, characterized in that: In step (4), the specific operation of sintering is: placing the ceramsite raw material particles in an oven, controlling the temperature to 105±5°C, and drying for 30-40 min; then placing the ceramsite raw material particles in a high-temperature furnace, adjusting the temperature to 500-600°C, and preheating for 30-40 min; after the preheating, adjusting the temperature to 1150-1250°C and sintering for 30-40 min; and reducing the temperature to room temperature at a rate of ≤3°C / min to obtain type A and type B boron nitride ceramsite.
6. The mass concrete with low hydration peak temperature according to claim 1, characterized in that: The municipal sludge and sludge are municipal sludge and sludge that have been filtered, adsorbed, precipitated and separated.
7. The mass concrete with low hydration peak temperature according to claim 1, characterized in that: The water content of the crushed and dried municipal sludge or mud is ≤1%, and the particle size is ≤0.8 mm.
8. The mass concrete with low hydration peak temperature according to claim 1, characterized in that: The boron nitride is one or more of hexagonal boron nitride, cubic boron nitride or wurtzite boron nitride. The boron nitride has a particle size of 5-50 μm, a purity of ≥99%, and an apparent density of 2300-3450 kg / m 3 .
9. The method for preparing a mass concrete with a low hydration peak temperature according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Pre-wetting the boron nitride ceramsite aggregate; S2, adding cement, sand, fly ash and slag powder into a concrete mixer in sequence and mixing them evenly; S3, adding crushed stone and boron nitride ceramsite aggregate into a concrete mixer and mixing them evenly; S4. Add the admixture into water, mix well, then pour into a concrete mixer and mix well to obtain a large volume concrete with a low hydration peak temperature.
10. The method for preparing a large volume concrete with a low hydration peak temperature according to claim 9, characterized in that: In step S1, the pre-wetting treatment time is 1 to 2 hours.
Citation Information
Cited By
Temperature self-balancing fine aggregate concrete and preparation method thereof
CN119930226A
